2014
DOI: 10.1155/2014/582039
|View full text |Cite
|
Sign up to set email alerts
|

Highights in the History of Epilepsy: The Last 200 Years

Abstract: The purpose of this study was to present the evolution of views on epilepsy as a disease and symptom during the 19th and the 20th century. A thorough study of texts, medical books, and reports along with a review of the available literature in PubMed was undertaken. The 19th century is marked by the works of the French medical school and of John Hughlings Jackson who set the research on epilepsy on a solid scientific basis. During the 20th century, the invention of EEG, the advance in neurosurgery, the discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 136 publications
0
41
0
14
Order By: Relevance
“…Cellular and molecular advances in the 20th century provided further insight into the production of seizures. This includes the use of animal models revealing that interictal discharges are associated with a paroxysmal depolarization shift and a superimposed burst of high‐frequency spikes in the cortical neurons and the evidence that generalized ictogenesis is related to hyperactivity in physiological functional anatomical networks as a result of an abnormal interaction of both cortical and subcortical mechanisms . This new knowledge was reflected in the 2010 seizure classification revision.…”
Section: Pathophysiology Of Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular and molecular advances in the 20th century provided further insight into the production of seizures. This includes the use of animal models revealing that interictal discharges are associated with a paroxysmal depolarization shift and a superimposed burst of high‐frequency spikes in the cortical neurons and the evidence that generalized ictogenesis is related to hyperactivity in physiological functional anatomical networks as a result of an abnormal interaction of both cortical and subcortical mechanisms . This new knowledge was reflected in the 2010 seizure classification revision.…”
Section: Pathophysiology Of Seizuresmentioning
confidence: 99%
“…Further techniques including functional MRI, positron emission tomography (PET), single‐photon emission computed tomography (SPECT), and magnetoencephalography (MEG) continued to make significant contributions to the detection of epileptogenic lesions. Along with this came the rise of epilepsy surgery and the use of modern techniques such as intracranial EEG and stereoelectroencephalography (sEEG) to precisely localize the epileptogenic zone . Neurosurgical methods have now advanced far beyond resection, employing to various extent procedures such as callosotomy, multiple subpial transection (MST), vagal nerve stimulator (VNS), or more recently responsive neurostimulator (RNS) for nonresectable epileptogenic lesions.…”
Section: Etiologiesmentioning
confidence: 99%
“…[4] From these early days, doctors understood that epilepsy is caused by abnormal electrical discharges in a specific part of the brain. This led to the premise that if that abnormal part of the brain can be resected, the epilepsy will be controlled.…”
Section: Cmementioning
confidence: 99%
“…Experimental animal studies showed that stimulation of the mesial temporal structures results in seizure attacks, while stimulation of the amygdala, the head of hippocampus and pyriform region in animals, produced arrested movement, licking, chewing and swallowing (2,3). In 1952, based on included anterior temporal lobectomy (ATL) with amygdalohippocampectomy (AH) and VNS, at HUSM in last 13 years; their surgeries took place between 2004 and 2011.…”
Section: Introductionmentioning
confidence: 99%